DISSECTING QUANTITATIVE TRAIT LOCI FOR AGRONOMIC TRAITS RESPONDING TO IRON DEFICEINCY IN MUNGBEAN [Vigna radiata (L.) Wilczek] - Somta, Prakit; Prathet, Prayoon; Kongjaimun, Alisa; Srinives, Peerasak (AGRIVITA, Journal of Agricultural Science, 2014)
Calcareous soil is prevalent in many areas of the world agricultural land causing substantial yield loss of crops. We previously identified two quantitative trait locus (QTL) qIDC3.1 and qIDC2.1 controlling leaf chlorosis in mungbean grown in calcareous soil in two years (2010 and 2011) using visual score and SPAD measurement in a RIL population derived from KPS2 (susceptible) and NM10-12-1 (resistant). The two QTLs together accounted for 50% of the total leaf chlorosis variation and only qIDC3.1 was confirmed, although heritability estimated for the traits was as high as 91.96%. In this study, we detected QTLs associated with days to flowering , plant height, number of pods per plants, number of seeds per pods, and seed yield per plants in the same population grown under the same environment with the aim to identify additional QTLs controlling resistance to calcareous soil in mungbean. Single marker analysis revealed 18 simple sequence repeat markers, while composite interval mapping identified 33 QTLs on six linkage groups (1A, 2, 3, 4, 5 and 9) controlling the five agronomic traits. QTL cluster on LG 3 coincided with the position of qIDC3.1, while QTL cluster on LG 2 was not far from qIDC2.1. The results confirmed the importance of qIDC3.1 and qIDC2.1 and revealed four new QTLs for the resistance to calcareous soil.Â